THE INFLUENCE OF PRODUCT PACKAGING AND SERVICE QUALITY ON CONSUMER PERCEPTION IN COFFEE SHOP (CASE STUDY ON TWENTIES COFFEE SHOP) - Mario Adriel Titah (Universitas Sam Ratulangi, 2022)
Improving the quality of customer service and product menu package design is a priority to focus on coffee shops. This study aims to analyze consumer perceptions of the product and service packages of Twenties coffee shops in Manado. This research is a type of quantitative research, which uses data obtained through questionnaires. The population of this research is people in Manado who have experience in the coffee industry, where the sample size is taken from 100 respondents who also have experience with coffee shops. The results of this study found that there is a positive relationship between product packaging and consumer perceptions. Mechanism of quality service has a significant effect on the level of consumer perception. Meanwhile, there is a positive influence that occurs between service quality and consumer perceptions where research finds that service quality increases consumer perceptions.